Inclusive communication of crisis information: An explorative study through participatory design with elderly - Hansenäs, Rosanna; Samuelsson, Sofia (My University, 2022)
With severe climate-related crises like flooding, storms, and wildfires increasing globally, authorities need to ensure that information reaches and supports all members of society. However, there is a risk that elderly, who might often have cognitive impairments, are excluded since channels for crisis information are largely based on audio and image. Using an exploratory approach, this master thesis investigated how information communicated to the elderly in future climate-related crises in Sweden can become more inclusive and create a feeling of safety. Methods for engaging the elderly in participatory research when investigating future scenarios and sensitive issues are explored and compared to reference literature and input from authorities. The study identified (1) the elderly living alone in cities with few social contacts, (2) those with impairments or (3) those who are less digital as groups as potentially critical user groups. To guide responsible authorities to meet the needs of these groups, a combination of guidelines and concept proposals of possible future ways of communication in crisis are suggested. The concepts proposed are an automatic voice SMS, an update of the outdoor signal "Hesa Fredrik'' communicated with drones to reach residents in the countryside and islands, and a chat group to support neighbourhood cooperation in crises. The concepts were described and supported with additional information in an updated version of the brochure "If Crisis or War Comes". In combination with the concepts, the guidelines can make crisis information more inclusive for all but need to be further revised and tested before implementation. In addition, the study can be used as a reference for future participatory research and investigation of methods to use when working with elderly on sensitive issues. It also opens for further exploration of simulating more severe future crisis scenarios with participants.
Keywords: Participatory design; Elderly; Seniors; Crisis information; Crisis communication; Climate-related crises; Design for Elderly; Design for all.